Electrode size influence on static and dynamic single cell lead-acid battery - Muhammad Ghufron; Kurriawan Budi Pranata; Istiroyah Istiroyah; Masruroh Masruroh; Cholisina Anik Perwita; Ahmad A. Amirullah; Nur Khairati; Yofinda Eka Setiawan; Fakhrusy R. Ramadhan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Renewable energy such as solar energy, waves and wind require batteries as a storage of electrical energy which still has constraints related to voltage, capacity, and energy efficiency. This experiment aims to determine the effect of electrode size on lead-acid dynamic and static battery capacity and energy efficiency. Dynamic and static single cell lead-acid batteries consist of three different electrode sizes, 13.5x7.5 cm2 (A1); 22.5x7.5 cm2 (A2) and 32.5x7.5 cm2 (A3) have been developed. Continuous and simultaneous charge-discharge test using turnigy accucell-6 50 w and chargemaster 2.02 software as graphic programming. Based on experiments, dynamic batteries perform better than static batteries with a difference in capacity of up to 48% and differences in energy efficiency up to 17%. The best performance is obtained on A3 dynamic batteries with an average capacity capacity of 10357 mAh and an average energy efficiency of 81%.